2020
DOI: 10.24875/ric.20000060
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Treatment Against Cervical Cancer

Abstract: Cervical cancer (CC) is one of the most common gynecological tumors and an important health problem, especially in developing countries. The vast majority of patients in early stages are cured of the disease with surgical treatment and with concomitant chemoradiotherapy in locally advanced stages. However, in patients with recurrent, persistent, or metastatic cervical CC, the effectiveness of treatment is limited, except for the combination of chemotherapy based on platinum doublets plus bevacizumab, the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Combination therapy with ICIs can overcome tumor resistance and improve treatment outcomes ( Patel and Minn, 2018 ; Zhang et al, 2022 ). It has now been shown that inhibitors of PD-1 and CTLA4 can harness the host immune system to achieve antitumor effects in the treatment of CC ( Jiménez-Lima et al, 2020 ; Wendel Naumann and Leath, 2020 ). Therefore, identifying patients who are candidates for ICI therapy in clinical practice is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy with ICIs can overcome tumor resistance and improve treatment outcomes ( Patel and Minn, 2018 ; Zhang et al, 2022 ). It has now been shown that inhibitors of PD-1 and CTLA4 can harness the host immune system to achieve antitumor effects in the treatment of CC ( Jiménez-Lima et al, 2020 ; Wendel Naumann and Leath, 2020 ). Therefore, identifying patients who are candidates for ICI therapy in clinical practice is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of durvalumab has also been reported to cause side effects such as pneumonitis, hepatitis, colitis or diarrhea, hypothyroidism, adrenal insufficiency, hypophysitis or hypopituitarism, type 1 diabetes, nephritis, and skin rash or dermatitis. Other side effects such as diarrhea, fatigue, and hypokalemia were observed in 35%, 25%, and 25% of cases, respectively ( 13 ).…”
Section: Advantages and Disadvantages Of Monoclonal Antibody Therapiesmentioning
confidence: 99%
“…Durvalumab (ImfinziTM; AstraZeneca) is a human monoclonal antibody that suppresses PD-L1, prevents it from interacting with PD-1, and increases the cytotoxic and anti-tumor activity of T cells ( 13 ). This antibody was approved by the FDA on May 1, 2017, due to its ORR in treating local metastatic or advanced urothelial cancer ( 85 ).…”
Section: Functions Of Monoclonal Antibodies Against Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations